KORELASI PENGETAHUAN DAN SIKAP IBU TERHADAP KONSUMSI MAKANAN MANIS DENGAN STATUS GIZI ANAK BALITA DI DESA LADANG TUHA, ACEH SELATAN TAHUN 2024 - nyak berlian, Cut; Febriansyah, M. Irfan; khairunnas; Apriani Hasanah Harahap , Laila (Universitas Cokroaminoto Palopo, 2025)
The nutritional status of preschool children is significantly influenced by dietary patterns, especially the excessive consumption of sugary foods. High-sugar foods increase the risk of undernutrition and other health complications. Maternal knowledge and attitudes towards nutrition play a crucial role in shaping children's eating habits. This study aimed to analyze the correlation between maternal knowledge and attitudes regarding sugary food consumption and the nutritional status of preschool children aged 1–5 years. A quantitative study with a cross-sectional design was conducted among 120 children, using purposive sampling. Data were collected through questionnaires and anthropometric measurements and analyzed using the Spearman correlation test. The results showed a significant positive correlation between maternal knowledge and children's nutritional status (r = 0.404, p < 0.001), and a significant negative correlation between maternal attitudes and nutritional status (r = –0.508, p < 0.001). These findings emphasize the importance of enhancing maternal nutrition education and promoting positive attitudes toward healthy food choices to improve the nutritional status of preschool children. foods, and not postponing meal schedules even in the midst of busy academic activities such as studying and working on final assignments.